Detection and Quantification of Cannabinoids in Extracts of Cannabis sativa Roots Using LC-MS/MS - Gul, Waseem; Gul, Shahbaz W.; Chandra, Suman; Lata, Hemant; Ibrahim, Elsayed A.; ElSohly, Mahmoud A. (Planta Medica, 2018)
A liquid chromatography-tandem mass spectrometry single-laboratory validation was performed for the detection and quantification of the 10 major cannabinoids of cannabis, namely, (−)-trans-Δ9-tetrahydrocannabinol, cannabidiol, cannabigerol, cannabichromene, tetrahydrocannabivarian, cannabinol, (−)-trans-Δ8-tetrahydrocannabinol, cannabidiolic acid, cannabigerolic acid, and Δ9-tetrahydrocannabinolic acid-A, in the root extract of Cannabis sativa. Acetonitrile : methanol (80 : 20, v/v) was used for extraction; d3-cannabidiol and d3- tetrahydrocannabinol were used as the internal standards. All 10 cannabinoids showed a good regression relationship with r2 > 0.99. The validated method is simple, sensitive, and reproducible and is therefore suitable for the detection and quantification of these cannabinoids in extracts of cannabis roots. To our knowledge, this is the first report for the quantification of cannabinoids in cannabis roots.
Keywords: Cannabis sativa; LC-MS/MS; quantification; cannabis roots; extracts; cannabinoids; Cannabaceae